Subclinical Systolic and Diastolic Dysfunction Is Evident in Youth With Elevated Blood Pressure. Issue 6 (June 2020) - Tran, Andrew H.; Flynn, Joseph T.; Becker, Richard C.; Daniels, Stephen R.; Falkner, Bonita E.; Ferguson, Michael; Hanevold, Coral D.; Hooper, Stephen R.; Ingelfinger, Julie R.; Lande, Marc B.; Martin, Lisa J.; Meyers, Kevin; et al.
Abstract : Hypertension is associated with cardiovascular events in adults. Subclinical changes to left ventricular strain and diastolic function have been found before development of decreased left ventricular ejection fraction and cardiovascular events. Our objective was to study effects of blood pressure (BP) on ventricular function in youth across the BP spectrum. Vital signs and labs were obtained in 346 participants aged 11 to 19 years who had BP categorized as low-risk (N=144; systolic BP <75th percentile), mid-risk (N=83; systolic BP ≥80th and <90th percentile), and high-risk (N=119; systolic BP ≥90th percentile). Echocardiography was performed to assess left ventricular strain and diastolic function. Differences between groups were analyzed by ANOVA. General linear models were constructed to determine independent predictors of systolic and diastolic function. Mid-risk and high-risk participants had greater adiposity and more adverse metabolic labs (lower HDL [high-density lipoprotein], higher glucose, and higher insulin) than the low-risk group. Mid-risk and high-risk participants had significantly lower left ventricular ejection fraction and peak global longitudinal strain than the low-risk group (both P ⩽0.05). The E/e′ ratio was higher in the high-risk group versus the low-risk and mid-risk groups, and the e′/a′ ratio was lower in the high-risk versus the low-risk group (both P ⩽0.05). BP and adiposity were statistically significant determinants of left ventricular systolic and diastolic function. Subclinical changes in left ventricular systolic and diastolic function can be detected even at BP levels below the hypertensive range as currently defined.